2017
DOI: 10.1021/jacs.6b12708
|View full text |Cite
|
Sign up to set email alerts
|

Direct C–H Cyanation of Arenes via Organic Photoredox Catalysis

Abstract: Methods for the direct C-H functionalization of aromatic compounds are in demand for a variety of applications, including the synthesis of agrochemicals, pharmaceuticals, and materials. Herein, we disclose the construction of aromatic nitriles via direct C-H functionalization using an acridinium photoredox catalyst and trimethylsilyl cyanide under an aerobic atmosphere. The reaction proceeds at room temperature under mild conditions and has proven to be compatible with a variety of electron-donating and -withd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(128 citation statements)
references
References 41 publications
(66 reference statements)
2
122
2
2
Order By: Relevance
“…In addition to these substrates from our prior amination report, we wanted to demonstrate that additional benzenoid compounds from our arene cyanation work 11 participated in the amination chemistry to expand the functional group tolerance of the reaction. Esters were compatible ( 2n ), as well as O -benzylphenols ( 2o ) and allyl substituents ( 2o and 2p ), even under aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these substrates from our prior amination report, we wanted to demonstrate that additional benzenoid compounds from our arene cyanation work 11 participated in the amination chemistry to expand the functional group tolerance of the reaction. Esters were compatible ( 2n ), as well as O -benzylphenols ( 2o ) and allyl substituents ( 2o and 2p ), even under aerobic conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The site selectivities observed when a variety of other azole nucleophiles were used ( 18c – g ) matched those reported above when using pyridines, quinolines, pyrazoles, indazoles, and benzofurans with pyrazole as the coupling partner. We also wanted to test whether other aryl functionalization reactions such as the C–H cyanation developed in our laboratory 11 followed similar site selectivities ( 18h and 18i ). The results in Figure 11 demonstrate that other nucleophiles exhibit the same site selectivities for a variety of heterocyclic classes as previously discussed, allowing the predictive model to be generalized to include a range of nucleophiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TMSCN is employed as the cyanide source, acridinium salts as the photocatalyst, under irradiation from blue LEDs and aerobic conditions (Scheme 34) [80]. The authors show a set of diverse molecules that underwent the transformation cleanly.…”
Section: Reviewmentioning
confidence: 99%
“…The 1 H NMR analysis showed that the product consists of only one regioisomer, and 2D NMR experiments confirmed that helicene 3 was functionalized only at the 6 position. The cyanation reaction was performed using a protocol reported by Nicewicz . In this case, the reaction was conducted under air atmosphere using an acridinium photocatalyst (10 mol %) in 10:1 mixture of acetonitrile pH 9 phosphate buffer, and trimethylsilyl cyanide (1.5 equiv) was used as the source of the −CN group.…”
Section: Resultsmentioning
confidence: 92%